Long-term cardiology outcomes in children after early treatment for Chagas disease, an observational study. - Nicolás Leonel González; Guillermo Moscatelli; Samanta Moroni; Griselda Ballering; Laura Jurado; Nicolás Falk; Andrés Bochoeyer; Alejandro Goldsman; María Grippo; Héctor Freilij; Facundo Garcia Bournissen; Eric Chatelain; et al. (Public Library of Science (PLoS), 2022)
Background Parasite persistence after acute infection with Trypanosoma cruzi is an important factor in the development of Chagas disease (CD) cardiomyopathy. Few studies have investigated the clinical effectiveness of CD treatment through the evaluation of cardiological events by long term follow-up of treated children. Cardiological evaluation in children is challenging since features that would be diagnosed as abnormal in an adult's ECG may be normal, age-related findings in a pediatric ECG trace. The objective was to evaluate cardiac involvement in patients with Chagas disease with a minimum follow-up of 6 years post-treatment. Methodology A descriptive study of a cohort of pediatric patients with CD treated with benznidazole (Bz) or nifurtimox (Nf) was conducted. Children (N = 234) with at least 6 years post CD treatment followed at the Parasitology and Chagas Service, Buenos Aires Children's Hospital (Argentina) were enrolled. By convenience sampling, children who attended a clinical visit between August 2015 and November 2019 were also invited to participate for additional cardiovascular studies like 24-hour Holter monitoring and speckle-tracking 2D echocardiogram (STE). Benznidazole was prescribed in 171 patients and nifurtimox in 63 patients. Baseline parasitemia data was available for 168/234 patients. During the follow-up period, alterations in routine ECG were observed in 11/234 (4.7%, 95% CI [2-7.4%]) patients. In only four patients, with complete right bundle branch block (cRBBB) and left anterior fascicular block (LAFB), ECG alterations were considered probably related to CD. During follow-up, 129/130 (99%) treated patients achieved persistent negative parasitemia by qPCR. Also decrease in T.cruzi antibodies titers was observed in all patients and negative seroconversion occurred in 123/234 (52%) patients. Conclusions A low incidence of cardiological lesions related to CD was observed in patients treated early for pediatric CD. This suggests a protective effect of parasiticidal treatment on the development of cardiological lesions and highlights the importance of early treatment of infected children. Trial registration ClinicalTrials.gov NCT04090489.